Excess Frequent Insufficient Sleep in American Indians/Alaska Natives. (21st February 2013) - Chapman, Daniel P.; Croft, Janet B.; Liu, Yong; Perry, Geraldine S.; Presley-Cantrell, Letitia R.; Ford, Earl S.
Abstract : Objective . Frequent insufficient sleep, defined as ≥14 days/past 30 days in which an adult did not get enough rest or sleep, is associated with adverse mental and physical health outcomes. Little is known about the prevalence of frequent insufficient sleep among American Indians/Alaska Natives (AI/AN). Methods . We assessed racial/ethnic differences in the prevalence of frequent insufficient sleep from the combined 2009-2010 Behavioral Risk Factor Surveillance Survey among 810, 168 respondents who self-identified as non-Hispanic white (NHW, n = 671, 448 ), non-Hispanic black (NHB, n = 67, 685 ), Hispanic (n = 59, 528 ), or AI/AN (n = 11, 507 ). Results . We found significantly higher unadjusted prevalences (95% CI) of frequent insufficient sleep among AI/AN (34.2% [32.1–36.4]) compared to NHW (27.4% [27.1–27.6]). However, the age-adjusted excess prevalence of frequent insufficient sleep in AI/AN compared to NHW was decreased but remained significant with the addition of sex, education, and employment status; this latter relationship was further attenuated by the separate additions of obesity and lifestyle indicators, but was no longer significant with the addition of frequent mental distress to the model (PR = 1.05; 95% CI : 0.99–1.13). This is the first report of a high prevalence of frequent insufficient sleep among AI/AN. These results further suggest that investigation of sleep health interventions addressing frequent mental distress may benefit AI/AN populations.